Knowledge, attitude, and perspective of dental students related to green dentistry: A Cross-Sectional Study. - Allana, Zeeshan; Asma Bashir; Tatheer Imran; Faizan Ahmed Siddiqui; Iqra Ali Muhammad; Mina Dar; Syeda Fizza Naqvi (International Journal of Endorsing Health Science Research, 2024)
Background: In an era marked by heightened environmental consciousness, Green Dentistry emerges as a pivotal approach, intertwining oral health with ecological responsibility. This study aims to explore the awareness, attitudes, and practices of green dentistry among dental students in Karachi, Pakistan. Methodology: A cross-sectional study was conducted among undergraduate and postgraduate dental students in Karachi using a structured questionnaire adapted from previous research. Data collection occurred through various online platforms, and statistical analysis was performed using SPSS version 23.0. Results: This study reveals varying levels of awareness among participants, with undergraduates (48.46%) generally exhibiting higher familiarity with Green Dentistry compared to postgraduates (27.04%). Factors influencing adoption include cost considerations and knowledge gaps. While promising trends in eco-friendly practices are noted, particularly in waste management, barriers such as time constraints persist. Conclusion: The study highlights a positive shift towards sustainable dentistry among emerging professionals in Karachi. Collaboration between institutions and policymakers is crucial for fostering eco-friendly practices. Future efforts should focus on targeted educational interventions and continuous evaluation to promote sustainable dental practices effectively. Integrating Green Dentistry principles into dental education and practice is essential for shaping a more environmentally conscious dental landscape in Karachi and beyond.